(untitled) (International Journal of Engineering Sciences & Management Research, 2014)
Information Technology (IT) had a great impact in all aspects of life such as economy, businesses and enterprises. The global economy is currently undergoing fundamental transformation in which IT plays a key role. IT has a real impact in most of industries and in all aspects of economy, while businesses and enterprises continue to undergo considerable changes. Usage of these technologies is revolutionizing the rules of business, resulting in structural transformation of enterprises. Modern businesses are not possible without help of information technology, which is having a significant impact on the operations of Small and Medium scale Business (SMB). It is claimed to be essential for the survival and growth of economies in general. SMB is drawing attention in developed and developing countries as well as in transition countries. It is generally recognized that SMB play a vital role in the revitalization and development of national economy in many countries and particular in the context of India. It is encouraging the development of SMB and the role that SMB sector can play in promoting economic and social development by creating opportunities for employment. These components are described and discussed while more research and studies on the adoption of information technology in SMB in India are proposed as necessary